Ovine RAP1GAP and rBAT gene polymorphisms and their association with tail fat deposition in Hu sheep - Ma, Zongwu; Wang, Weimin; Zhang, Deyin; Zhang, Yukun; Zhao, Yuan; Li, Xiaolong; Zhao, Liming; Lin, Changchun; Wang, Jianghui; Zhou, Bubo; Cheng, Jiangbo; Xu, Dan; et al. (Frontiers in Veterinary Science, 2022)
The excessive deposition of tail fat will seriously restrict the commercial value of mutton, affect the feed efficiency and increase the feeding cost. The purpose of this study was to identify the single nucleotide polymorphisms (SNPs) of RAP1GAP and rBAT genes by PCR amplification and Sanger sequencing, the SNPs were genotyped by KASP genotyping assays to evaluate their association with tail fat deposition traits. The result showed that two synonymous mutations g.13561 G＞A and g.1460 T>C were found in RAP1GAP and rBAT, respectively, and there are three genotypes GG, AG, AA and CC, CT, TT at these two loci, respectively. Association analysis showed that g.13561 G＞A of RAP1GAP was associated with tail width, tail fat weight and relative tail fat weight (P < 0.05). The g.1460 T>C of rBAT was associated with tail width and tail fat weight (P < 0.05). Different combinations of genotypes also differed significantly with tail fat deposition traits. In the tail fat tissue, the expression levels of RAP1GAP was significantly higher in small-tailed sheep than in big-tailed sheep, and the expression levels of rBAT was significantly higher in big-tailed sheep than in small-tailed sheep. In the liver, the expression levels of RAP1GAP and rBAT was significantly higher at 6 months than at 0 and 3 months. In conclusion, RAP1GAP and rBAT polymorphisms can be used as a candidate molecular marker to reduce tail fat deposition in sheep.